2020
DOI: 10.1159/000507331
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prealbumin and Echocardiography Parameters Predict Mortality in Peritoneal Dialysis Patients

Abstract: <b><i>Aim:</i></b> Protein-energy malnutrition and cardiovascular (CV) disease predisposes patients with end-stage renal disease (ESRD) on dialysis to a high risk of early death, but the prognostic value of prealbumin (PAB) and echocardiographic indices in ESRD patients treated with maintenance peritoneal dialysis (PD) remains unclear. <b><i>Methods:</i></b> A total of 211 PD patients (mean age 49.2 ± 15.4 years, 51.7% male) were prospectively studied. PAB and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Our results showed some characteristics of PD patients relating to mortality, including hypertension, overweight, and obesity, DM, hypoprealbuminia, and anemia (Table 2 , 3 ). Some previous studies have also confirmed the fact [ 36 - 39 ]. Thus, hypertension, DM, overweight, and obesity are risk factors and causes of many complications such as cerebrovascular disorders, myocardial ischemia, and peripheral artery disease.…”
Section: Discussionsupporting
confidence: 68%
“…Our results showed some characteristics of PD patients relating to mortality, including hypertension, overweight, and obesity, DM, hypoprealbuminia, and anemia (Table 2 , 3 ). Some previous studies have also confirmed the fact [ 36 - 39 ]. Thus, hypertension, DM, overweight, and obesity are risk factors and causes of many complications such as cerebrovascular disorders, myocardial ischemia, and peripheral artery disease.…”
Section: Discussionsupporting
confidence: 68%
“…Patients initiating USPD may have severe symptoms of uremia [20]; besides, systemic inflammation with the activation of complements, elevated protein catabolism, and aggravated protein malnutrition may lead to poor patient outcomes [21]. Protein-energy malnutrition predisposes ESRD patients initiating dialysis to a high risk of early death [22]. Moreover, hypoproteinemia is a marker of poor general health [23].…”
Section: Discussionmentioning
confidence: 99%